Analiza statystyczna użytkowania systemu SEKAP w woj. śląskim - Sikora, Konrad (Wydawnictwo Uniwersytetu Rzeszowskiego, 2011)
Stopniowe wdrażanie systemów informatycznych m.in. takich jak SEKAP oraz ich integracja z coraz bardziej powszechnymi elektronicznymi kanałami komunikacyjnymi pozwala na możliwość świadczenia usług elektronicznych w administracji publicznej na coraz wyższym poziomie. Dzięki realizacji Projektu SEKAP podniósł się poziom świadomości społeczeństwa w woj. śląskim w zakresie usług świadczonych drogą elektroniczną oraz zwiększa się efektywność pracy administracji m.in. w zakresie realizacji tych usług na terenie powiatów biorących udział w projekcie.

SEKAP – is a long expected teleinformatic environment which is providing public services in Information Society. This is a strategic project for development communes and counties of Silesia Region. The project contents: creation of teleinformatic environment, analytic activities related to preparation of implementation this environment and the management of actions related to providing public services. The implementation of that project will enable to modernize the local government institution by increasing usage new information and communication technologies and also by implementation documents circulation’s system with electronic archive. Those activities will make able to create e-Government. In the article has been presented the statistic of survey made in a period from January 2009 to March 2011. The survey concerned usability of SEKAP by logged in users from different regions in Poland. The statement was made according data from Silesian Center of Information Society. In the article have been placed information about: number of visits on web side SEKAP, number of electronic applications made by private users and companies from 2009 to 2011. The author is trying to prove the thesis, that using web side www.sekap.pl provides a lot of advantages for users. The article treats also about greater reformation of communication citizen-government-trader.